The Innovation of Waqf Andragogy Amidst ‘Kampus Merdeka’ Era - Sulistyowati; Bayu Taufik Possumah; Nurul Huda; Siti Nur Indah Rofiqoh; Zulfison (Department of Islamic Economics, Islamic University of Indonesia, 2022)
Waqf, as a unique Islamic legacy, has been practiced since the Prophets Muhammad Era. Unfortunately, society’s understanding of waqf is not yet comprehensive and accurate, mainly at the higher education level. The study aims to provide the innovative andragogical formulation for higher education institutions regarding the ‘Kampus Merdeka’ enforcement and to explore the breakthroughs in waqf curriculum by academicians in universities during the KKM era. Focused Group Discussion (FGD) and semi-structured in-depth interviews are conducted to gather the primary data from the relevant respondents such as regulators, academicians, practitioners, and students. Initially, the desk study is used as a literature review from various sources to obtain prior knowledge related to the topic investigated. Findings of this study have revealed that Waqf stakeholders identified several innovative methods in the form of creative implementation such as Reshaping of National Standard Waqf Curriculum, Link and Match of Waqf Education with the Waqf DUDI, Waqf Literacy Relevant Movement, and IT and Waqf Digital Engagement. Thus, this study recommends a point regarding its result that some challenges have to be tackled altogether by the stakeholders in terms of educator capacity and the lack of human resources from the practitioner to undertake massive socialization with the adult learner. This research result could be implemented in the higher education institution that teaches waqf and other instruments of Islamic Social Finance (ISF) as one of the subjects in the Islamic Economic curriculum.